Interdisciplinary working in public health research: a proposed good practice checklist. (14th March 2017) - Gavens, L; Holmes, J; Bühringer, G; McLeod, J; Neumann, M; Lingford-Hughes, A; Hock, E S; Meier, P S
Abstract: Background: Guidance on how different disciplines from the natural, behavioural and social sciences can collaborate to resolve complex public health problems is lacking. This article presents a checklist to support researchers and principle investigators to develop and implement interdisciplinary collaborations. Methods: Fourteen individuals, representing 10 disciplines, participated in in-depth interviews to explore the strengths and challenges of working together on an interdisciplinary project to identify the determinants of substance use and gambling disorders, and to make recommendations for future interdisciplinary teams. Data were analysed thematically and a checklist was derived from insights offered by participants during interview and discussion among the authors on the implications of findings. Results: Participants identified 18 scientific, interactional and structural strengths and challenges of interdisciplinary research. These findings were used to develop an 18-item BASICS checklist to support future interdisciplinary collaborations. The five domains of the checklist are: (i) B lueprint, (ii) A ttitudes, (iii) S taffing, (iv) I nteractions and (v) C ore S cience. Conclusion: Interdisciplinary work has the potential to advance public health science but the numerous challenges should not be underestimated. Use of a checklist, such as BASICS, when planning and managing projects may help future collaborations to avoid some of the common pitfalls of interdisciplinary research.